Effect of Different Leaf Litters on Carbon, Nitrogen and Microbial Activities of Sodic Soils. (25th August 2014) - Singh, Kripal; Trivedi, Pragya; Singh, Geetu; Singh, Bajrang; Patra, Dharani Dhar
Abstract: This study investigates the effect of single leaf litter of Terminalia arjuna (Ta) and Prosopis juliflora (Pj), mixed leaf litters [Ta, Pj, Azadirachta indica (Ai) and Albizia procera (Ap)] and paddy straw (Ps; Oryza sativa ) on chemical properties and microbial activities of slightly sodic (SS), moderately sodic (MS) and highly sodic (HS) soils during 1 year in vitro decomposition process. For this purpose, equal amount (60 g) of single leaf litter [Ta (C : N = 43) and Pj (C : N = 38)], mixed leaf litters [1/4 of Ta, Pj, Ai and Ap (C : N = 30)] and Ps (C : N = 107) was added to equal amount (600 g) of SS, MS and HS soils. After addition of litters, changes in soil organic carbon (SOC), available nitrogen (Nav ), microbial biomass carbon, nitrogen, soil respiration, microbial quotient (Cmic  : Corg ) and metabolic quotient ( q CO2 ) were observed at 2 months intervals for the whole year in greenhouse at constant soil moisture. The respective annual increase, at the end of the experiment, in SOC and Nav was highest in MS soil (40% and 45%), whereas soil microbial biomass and soil respiration showed decreasing trend from HS soil (39% and 29%) to SS soil (28% and 21%). The highest SOC was mineralized in the MS (42%) and HS (32%) soils containing litter of Ta; although greater (20%) accumulation of SOC in SS soil was noticed with mixed leaf litters. The study reveals that MS and HS soils comparatively showed fast decomposition of litters and significant increase in carbon, nitrogen and microbial activities. Copyright © 2014 John Wiley & Sons, Ltd.